Has the stability and growth pact impeded political budget cycles in the European Union? - Mark Mink; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2005)
This paper examines whether there is a political budget cycle (PBC) in countries in the euro area. Using a multivariate model for the period 1999-2004 and various election indicators we find strong evidence that the Stability and Growth Pact has not restricted fiscal policy makers in the euro area in pursuing expansionary policies before elections. In an election-year – but not in the year prior to the election – the budget deficit increases. This result is in line with third generation PBC models, which are based on moral hazard. We also find a significant but small partisan effect on fiscal policy outcomes.
Keywords: D78; E62; D72; 330; fiscal policy; political budget cycle; Stability and Growth Pact; Finanzpolitik; Politischer Konjunkturzyklus; EU-Stabilitätspakt; Moral Hazard; Schätzung; Europäische Wirtschafts- und Währungsunion; EU-Staaten